Posture control characteristics of different age groups in China based on Bertec® balance advantage CDP/IVR—a cross-sectional study - He, Yaqi; Zhang, Pei; Li, Qing; Peng, Zhongmei; Gao, Jinpeng; Liu, Yang; Yang, Fan; Tian, Ye; Lv, Xianglin; Qian, Jinghua (Frontiers in Neurology, 2025)
ObjectiveTo establish the first normative dataset for postural control in Chinese adults using Bertec® CDP and to explore potential cross-cultural differences in aging trajectories by comparing with Western population data.MethodsThis cross-sectional study recruited 48 healthy Chinese adults stratified into four age decades (18–35, 36–45, 46–60, and 61–75 years). Participants attended three laboratory visits: the first two for screening and task familiarization, and the third for formal testing on the sensory organization test (SOT) and rhythmic weight shift (RWS) using computerized dynamic posturography (CDP), with 3–7 days between visits. Data were analyzed using one-way ANOVA with post-hoc tests. Exploratory comparisons with Danish normative data were conducted using one-sample T-tests.ResultsSignificant age-related declines were observed in the Composite Score (CS: rs = −0.532, p < 0.001), Visual Score (VIS: rs = −0.530, p < 0.001), and Vestibular Score (VEST: rs = −0.430, p = 0.002). ANOVA revealed significant inter-group differences in Equilibrium Scores (SOT2: p = 0.012; SOT3: p = 0.017; SOT4: p < 0.001; SOT5: p = 0.009; SOT6: p = 0.002) and CS (p = 0.001). Sensory scores showing parallel reductions (VIS: p < 0.001; VEST: p = 0.020; Preference, PREF: p = 0.018).RWS results demonstrated strong negative age-correlations for Directional Control (coronal: rs = −0.521, p < 0.001; sagittal: rs = −0.630, p < 0.001) and coronal Movement Velocity (rs = −0.398, p = 0.004), supported by significant inter-group differences in both planes (coronal: p = 0.002; sagittal: p < 0.001).ConclusionPostural control demonstrated a significant age-related decline in this cohort. Notably, individuals over 45 years exhibited a diminished capacity to integrate visual and vestibular information for complex balance tasks and visually guided motor control. This study provides essential normative data for clinical assessment in the Chinese population and underscores the need for population-specific benchmarks.